2009
DOI: 10.1007/s00330-009-1391-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance pancreatography: comparison of two- and three-dimensional sequences for assessment of intraductal papillary mucinous neoplasm of the pancreas

Abstract: The purpose was to compare two-dimensional (2D) magnetic resonance pancreatography (MRP) with 3D MRP to evaluate intraductal papillary mucinous neoplasm (IPMN). Thirty-four patients (22 men, 12 women; age range, 45-80 years) with IPMN (n = 40) were examined with MRP on 2D and 3D sequences. Two readers independently reviewed the images to assess the overall image quality, artifacts, lesion location, communication with main pancreatic duct, and potential for malignancy. The readers assigned their confidence leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Furthermore, the evaluation of pancreatic lesions by EUS is more invasive and largely dependent on the experience of the individual examiner as well as the anatomical conditions of the patient [24] . Limitations of pancreatic MRI include the long duration of the examination as well as movement artefacts [25] . Therefore, abdominal CT scans will likely remain important components of the diagnostic workup for pancreatic IPMN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the evaluation of pancreatic lesions by EUS is more invasive and largely dependent on the experience of the individual examiner as well as the anatomical conditions of the patient [24] . Limitations of pancreatic MRI include the long duration of the examination as well as movement artefacts [25] . Therefore, abdominal CT scans will likely remain important components of the diagnostic workup for pancreatic IPMN.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of CT scan and MRI in differentiating mucinous from non-mucinous cyst was 71% and 84% respectively, while the accuracy of CT vs MRI in differentiating benign from malignant cyst was 75-78% vs 78-86% (not statistically significant) [35]. Recently, 3D MRCP was shown to improve the image quality of pancreatic cysts [36]. However, 3D MRCP had similar diagnostic performance to 2D MRCP in differentiating benign from malignant cysts [37].…”
Section: Role Of Imaging In Diagnosing Pancreatic Cystic Lesionsmentioning
confidence: 99%
“…Certain studies have compared 2D and 3D MRCP for the visualization of the pancreatobiliary system (1–12). However, studies that have compared the use of 2D and 3D MRCP for the visualization of pancreatic cystic lesions focused solely on intraductal papillary mucinous neoplasm (IPMN) (5,8). The two previous studies concluded that image quality of the pancreatic duct of 3D MRCP was superior to that of 2D MRCP, 3D MRCP identified the morphological details of IPMN with more confidence compared with 2D MRCP.…”
Section: Introductionmentioning
confidence: 99%